2023
DOI: 10.18860/ling.v17i2.16673
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical Alliance and Pivot System of Batak Simalungun Language: A Syntactic Typology Study

Abstract: Syntax, morphology, and phonology can be used as a reference for language classification. This research aims to determine the grammatical alliance of the Simalungun language syntactically and its typology. It is a qualitative study with the typology approach. The data are phrases and clauses of the Simalungun language collected from informants and books – Simalungun language syntax books, by interviews and notes. It found that a transitive verb formulates the intransitive clause of the Simalungun Batak languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…Similarly, as stated by (Primus, 2015;Sinaga & Mulyadi, 2023), traditionally, grammatical relations are arguments that have a relationship with verbs. Arguments can be categorized to entail a relationship with a verb since the verb acts as the core of the syntactic process (Oghoghophia Famous, 2021).…”
Section: Introductionmentioning
confidence: 80%
“…Similarly, as stated by (Primus, 2015;Sinaga & Mulyadi, 2023), traditionally, grammatical relations are arguments that have a relationship with verbs. Arguments can be categorized to entail a relationship with a verb since the verb acts as the core of the syntactic process (Oghoghophia Famous, 2021).…”
Section: Introductionmentioning
confidence: 80%
“…His research interests are Sintaxis, Pragmatic, and Semantic. His corresponding email: Mulyadi@usu.ac.id Mubshirah and Mulyadi (2024)…”
Section: Acknowledgementmentioning
confidence: 99%
“…(Basaria, 2013)' s study showed that Pakpak-Dairi (PDL) is a language of the accusative case. (Sinaga & Mulyadi, 2023), Their research showed that the grammatical alliance system of the Simalungun language considers subject (S) and agent (A) identically. At the same time, predicate (P) is treated differently.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Rizki & Pujiati (2017), pivot merupakan kategori yang menghubungkan Subjek (S), Agen (A) dan Pasien). Dalam menggunakan uji pivot, perlu untuk mengetahui apakah jenis kalimat dalam bahasa tersebut termasuk transitif atau intransitif (Sinaga & Mulyadi, 2022).…”
Section: Pendahuluanunclassified